IL7RA single nucleotide polymorphisms are associated with the size and function of the MAIT cell population in treated HIV-1 infection - Han, Fei; Gulam, Muhammad Yaaseen; Zheng, Yichao; Zulhaimi, Nurul Syuhada; Sia, Wan Rong; He, Dan; Ho, Amanda; Hadadi, Leila; Liu, Zhenyu; Qin, Peiwu; Lobie, Peter E.; Kamarulzaman, Adeeba; et al. (Frontiers in Immunology, 2022)
MAIT cells are persistently depleted and functionally exhausted in HIV-1-infected patients despite long-term combination antiretroviral therapy (cART). IL-7 treatment support MAIT cell reconstitution in vivo HIV-1-infected individuals and rescue their functionality in vitro. Single-nucleotide polymorphisms (SNPs) of the IL-7RA gene modulate the levels of soluble(s)IL-7Rα (sCD127) levels and influence bioavailability of circulating IL-7. Here we evaluate the potential influence of IL-7RA polymorphisms on MAIT cell numbers and function in healthy control (HC) subjects and HIV-1-infected individuals on long-term cART. Our findings indicate that IL-7RA haplotype 2 (H2*T), defined as T-allele carriers at the tagging SNP rs6897932, affects the size of the peripheral blood MAIT cell pool, as well as their production of cytokines and cytolytic effector proteins in response to bacterial stimulation. H2*T carriers had lower sIL-7Rα levels and higher MAIT cell frequency with enhanced functionality linked to higher expression of MAIT cell-associated transcription factors. Despite an average of 7 years on suppressive cART, MAIT cell levels and function in HIV-1-infected individuals were still significantly lower than those of HC. Notably, we observed a significant correlation between MAIT cell levels and cART duration only in HIV-1-infected individuals carrying IL-7RA haplotype 2. Interestingly, treatment with sIL-7Rα in vitro suppressed IL-7-dependent MAIT cell proliferation and function following cognate stimulations. These observations suggest that sIL-7Rα levels may influence MAIT cell numbers and function in vivo by limiting IL-7 bioavailability to MAIT cells. Collectively, these observations suggest that IL-7RA polymorphism may play a significant role in MAIT cell biology and influence MAIT cells recovery in HIV-1 infection. The potential links between IL7RA polymorphisms, MAIT cell immunobiology, and HIV-1 infection warrant further studies going forward.